Exploring the Determinants of Food Insecurity in Pakistan - Shair, Waqas; Afzal, Haleema; Ahmad, Aftab; Iftikhar, Rabea (Pakistan Journal of Humanities and Social Sciences, 2024)
This research investigates the impact of various socioeconomic, demographic, and contextual factors on household food insecurity in Pakistan, utilizing data from the Pakistan Social and Living Standards Measurements (PSLM) 2019-20. The aftermaths of the Logistic regression analysis emphasize the vulnerability of households to food insecurity, influenced by factors such as literacy levels, income status, gender, marital status and age of the household head, as well as household size and migration status. Households headed by illiterate, lower-income, larger families, and migrants are particularly at risk. Conversely, households headed by older individuals, married couples, females, or those in higher income brackets are likely to experience higher food security due to more stable incomes and better resource management. These results point to the need for specific interventions that target educational and economic enhancements and address demographic vulnerabilities to improve food access and security for diverse groups.